Fire, Disease and Water in Ottawa: An Introduction - Taylor, John (Urban History Review / Revue d'histoire urbaine, 1979)
By the end of the nineteenth century control of fire and disease had become a scientific and technical reality that opened the way to a social transformation in the city. To effect such control, however, imposed a series of demands on urban politicians, among them one for an adequate supply of pure water. In Ottawa, the response to the new and necessarily collective imperatives was pinched, niggardly and slow. Much of the explanation—as the three papers that follow suggest—lay in politics, especially in its socio-economic base and ideological attitudes.